WAYS TO DEVELOP THE USE OF ISLAMIC FINANCE INSTRUMENTS (World Bulletin of Social Sciences, 2024)
This article outlines key strategies for the development of the Islamic finance industry. It emphasizes the importance of regulatory frameworks, innovation, capacity building, market infrastructure, standardization, ethical finance principles, global integration, awareness, education, and policy support. By addressing these areas, the Islamic finance industry can expand its reach, enhance its offerings, and contribute to financial inclusion and sustainable economic development.
Keywords: Regulatory frameworks; Innovation; Awareness; Education